2014
DOI: 10.4178/epih/e2014027
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Dense Breasts using Screening Mammography in Korean Women: a Retrospecitive Observational Study

Abstract: OBJECTIVES:This retrospective observational study evaluated the distribution of dense breasts by age group among healthy Korean women.METHODS:Participants were women aged 30 years and older who voluntarily underwent screening mammography between January 2007 and December 2011. Women who received the Breast Imaging Reporting and Data System for mammographic density of 3 or 4 were defined as having dense breasts. The proportion of women with dense breasts (PDB, %) was calculated by dividing the number of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, MG has some limitations, including exposure to radiation and a relatively high rate of false-positive results (22-24). More importantly, its performance is worse in young women and in women with heterogeneously dense or extremely dense breasts, which are highly prevalent among women from Asian countries such as Malaysia, Korea, and China (25)(26)(27). Therefore, researchers in these countries have been searching for new methods to substitute MG. HHUS is the primary tool for breast cancer screening in some Asian countries; however, little evidence has shown its effectiveness and accuracy (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, MG has some limitations, including exposure to radiation and a relatively high rate of false-positive results (22-24). More importantly, its performance is worse in young women and in women with heterogeneously dense or extremely dense breasts, which are highly prevalent among women from Asian countries such as Malaysia, Korea, and China (25)(26)(27). Therefore, researchers in these countries have been searching for new methods to substitute MG. HHUS is the primary tool for breast cancer screening in some Asian countries; however, little evidence has shown its effectiveness and accuracy (13).…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, breast densities and the proportion of younger women with breast cancer are higher than those in Western countries 18 . Asian women tend to have small and dense breasts, factors known to reduce the diagnostic accuracy of mammography 19 21 . Also, the peak age of breast cancer diagnosis in Asian women (Chinese, Korean, and Japanese) is between 45 and 55 years old, about 10–20 years younger than that in Caucasian women 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with the findings of a previous study that reported breast cancer with a shorter sojourn time (ST) and more aggressive progression among younger women [ 6 ]. These findings suggest that in Korean women, the strategy of screening for breast cancer for the age group of 30 to 39 years should be different from that used for the other age groups [ 8 , 17 - 19 ]. In other words, these findings are the rationale for the suggestion of shorter screening intervals in the younger age group [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a strategy for a screening program should be suggested for the age group of 30 to 39 years, in particular. Because the incidence rate of breast cancer is increasing, the suggested screening guidelines for the early detection of breast cancer in Korean women should be adapted regularly on the basis of the related evidence obtained from Korean women [ 8 , 17 - 19 , 21 ]. Thus, an additional study for the direct estimation of MST in breast cancer using Monte Carlo-Markov models should be performed after obtaining nationwide information on the sensitivity by age group to correctly interpret the results of this study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%